2016
DOI: 10.4067/s0717-95022016000200033
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Analysis of the Inferior Vena Cava Related to Lumbar Vertebra and the Aortic Bifurcation on Multidetector Computed Tomography (MDCT)

Abstract: SALBACAK, A.; AKIN, D.; KABAKCI, A. D. A.; YILMAZ, M. T.; CICEKCIBASI, A. E. & OZBEK, O.Morphometric analysis of the inferior vena cava related to the lumbar vertebra and the aortic bifurcation on multidetector computed tomography (MDCT). Int. J. Morphol., 34(2):620-627, 2016. SUMMARY:Vascular structures are in greater danger during lumbar surgery. The purpose of this study is to describe the morphology of the inferior vena cava (IVC) related to the lumbar vertebra and aortic bifurcation (AB) and assessing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…All details regarding the selection of eligible studies are presented in Figure 4 (PRISMA flow diagram). Eventually 31 articles were found eligible and were [11,15], 1 multidetector computed tomography (MDCT) study [20], 1 was angiographic study [38] and 1 was based on pelvic arteriograms [25]. Mean age or age range where included when available.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…All details regarding the selection of eligible studies are presented in Figure 4 (PRISMA flow diagram). Eventually 31 articles were found eligible and were [11,15], 1 multidetector computed tomography (MDCT) study [20], 1 was angiographic study [38] and 1 was based on pelvic arteriograms [25]. Mean age or age range where included when available.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Those works are mainly analyzing the levels of bifurcation of the aorta, iliac veins, confluence with the inferior vena cava (IVC), and relations between those structures. What’s more, veins not only occur in great variability in lumbar location [ 4 , 6 , 7 , 16 ], but also the measurements of venous structures are imprecise because of variations in blood flow and diameter associated with respiration [ 11 ]. That is why we decided to base our study on the relation between spinal column and arterial vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Cadaver study by Panagouli et al [ 21 ] also confirmed our findings—mean level of bifurcation was the lower third of the L4 vertebral body. As aforementioned, there is variability of venous structures in the lumbar region that lead to discrepancies in different studies [ 4 , 6 , 7 , 15 , 16 ]. Some authors reported aorta bifurcation 1–2 segments above the IVC confluence [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Where t is the section thickness, SU the scale unit of the printed film, d the distance between the test points of the grid, SL the measured length of the scale printed on the film and ∑p is the total number of points hitting the sectioned cut surface areas of the structure (Mahato, 2013;Wang et al, 2015;Azu et al;Keskinoz et al, 2016). According to this volumetric technique, a square grid of test points was positioned on each MRI, and all points hitting the structure were counted (Fig.…”
Section: Anatomical Measurements By a Universal Dicom Viewermentioning
confidence: 99%